Efficacy and safety of combined targeted therapy and immunotherapy versus targeted monotherapy in older patients with uHCC - Li, Yu; Zhong, Jian-Hong; Zhu, Xiao-Dong; Han, Chuang-Ye; Wang, Jia-Bei; Liu, Hong-Zhi; Hu, Kuan; Pan, Yang-Xun; Sun, Hui-Chuan; Peng, Tao; Liu, Lian-Xin; Zeng, Yong-Yi; et al. (Frontiers in Oncology, 2025)
BackgroundThe prevalence of hepatocellular carcinoma (HCC) among older patients is rising due to the aging population. This study aimed to compare the efficacy and safety of targeted therapy alone versus its combination with immunotherapy in older patients (≥ 65 years old) with unresectable HCC (uHCC).MethodsWe retrospectively analyzed 158 patients aged ≥ 65 diagnosed with uHCC who received targeted therapy alone or in combination with immunotherapy from the CLEAP database between March 2019 and July 2023. The primary endpoint was overall survival (OS), with secondary endpoints including progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and safety assessments for adverse events (AEs).ResultsThe ORR was 3.6% in the targeted monotherapy group compared to 29.4% in the combination therapy group, while the DCRs were 53.6% and 54.9%, respectively. Survival analysis indicated a median PFS of 7.3 months for monotherapy versus 13.2 months for combination therapy (P = 0.137) and a median OS of 16.0 months versus 20.0 months, respectively (P = 0.140). AEs occurred in 44.6% of the monotherapy group and 58.8% in the combination therapy group, with 20.5% in the combination group withdrawing due to adverse reactions, significantly higher than in monotherapy group.ConclusionAmong older patients with uHCC, the combination therapy demonstrated higher ORR and longer PFS and OS, although it had higher incidences of AEs and drug withdrawal.